Synergistic effect of exogeneous and endogeneous electrostimulation on osteogenic differentiation of human mesenchymal stem cells seeded on silk scaffolds. Issue 4 (7th October 2015) - Çakmak, Anıl S.; Çakmak, Soner; White, James D.; Raja, Waseem K.; Kim, Kyungsook; Yiğit, Sezin; Kaplan, David L.; Gümüşderelioğlu, Menemşe
ABSTRACT: Bioelectrical regulation of bone fracture healing is important for many cellular events such as proliferation, migration, and differentiation. The aim of this study was to investigate the osteogenic differentiation potential of human mesenchymal stem cells (hMSCs) cultivated on silk scaffolds in response to different modes of electrostimulation (e.g., exogeneous and/or endogeneous). Endogeneous electrophysiology was altered through the use of monensin (10 nM) and glibenclamide (10 μM), along with external electrostimulation (60 kHz; 100–500 mV). Monensin enhanced the expression of early osteogenic markers such as alkaline phosphatase ( ALP ) and runt‐related transcription factor 2 ( RUNX‐2 ). When exogeneous electrostimulation was combined with glibenclamide, more mature osteogenic marker upregulation based on bone sialoprotein expression (BSP) and mineralization was found. These results suggest the potential to exploit both exogeneous and endogeneous biophysical control of cell functions towards tissue‐specific goals. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:581–590, 2016.